Peningkatan Tata Kelola pada Sistem Manajemen Persediaan melalui Edukasi dan Pelatihan bagi UMKM di Desa Wisata Wates Jaya, Kabupaten Bogor - Muliani, Lila; Suprayitno, Degdo; Hidayat, Yusup Rachmat (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as one of the pillars of the national economy and provide significant employment opportunities. MSMEs located in tourist villages also play a crucial role. In the tourism sector, tourist villages also act as key drivers of economic growth. Therefore, MSMEs and tourist villages are interconnected in a mutually reinforcing relationship. In the tourism activity framework known as the 3S concept (something to see, something to do, something to buy), MSMEs serve as the primary actors in the